TRANSFORMASI GEN SUCROSE PHOSPHATE SYNTHASE (SoSPS1) MENGGUNAKAN Agrobacterium tumefaciens UNTUK MENINGKATKAN SINTESIS SUKROSA PADA TANAMAN TEBU (Saccharum officinarum L.) - Miswar; Bambang Sugiharto; Joedoro Soedarsono; Sukarti Moeljapawiro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Sucrose phosphate synthase (SPS; EC 2.3.1.14) plays an important role in partition of assimilated carbon in most plants. SPS catalyses the penultimate reaction in the pathway of sucrose synthesis, in which sucrose-6-phosphate (Suc6P) is synthesized from UDPglucose (UDPG) and fructose-6-P (Fru6P). To increase the capacity of sugarcane in sucrose synthesis, spindle leaves of sugarcane cv R579 were transformed with cDNA SoSPS1 from sugarcane under the control of constitutive promoter (35S CaMV) that constructed in pBI 121 (pKYS) using Agrobacterium tumefaciens. Based on PCR analysis, we have detected the existence of SPS transgene in some lines of transformed sugarcane, called line 4, 5, 6, and 7. The SPS transgene in transformed sugarcane could be expressed into translation level and increased the amount of leaves SPS protein, so the activity of leaves SPS was higher than wild type sugarcane as control. The transformed sugarcane line 4, 5, 6, and 7 showed 1.4–2.9 fold increases in SPS activity and 1,76–2,2 fold increases in leaves sucrose content. Increasing in SPS activity in transgenic sugarcane was coupled by the increase in invertase activity and ratio between sucrose and starch content.